Building an entrepreneurial and collaborative community for creating impact at the entrepreneurial and engaged university - Akpinar, Murat (2024)
The entrepreneurial and engaged university concept calls for utilizing the university’s knowledge to create economic and social impact. Its accomplishment, however, is challenging and thus requires an investigation. This research responds to this call first by exploring the ways that the concept can be realized at the graduate school of education and second by studying what kind of leadership is needed for successfully implementing it. The empirical study was guided by a framework developed from the literature review. It employed the case study research strategy, and the selected case is the Harvard Graduate School of Education. Qualitative data from multiple reliable sources was analyzed using the method of theoretical thematic analysis. The empirical study revealed four findings for the graduate school of education. First, adopting the broad-sense definition of the entrepreneurial and engaged university concept is more appropriate. Second, the impact extends to the country and the world, thus it is not limited to the region. Third, the observed ways to implement the concept are entrepreneurship by students, providing entrepreneurship training, consulting and training leaders in the industry, and conducting transformative research. Fourth, successfully implementing the entrepreneurial and engaged university concept demands both entrepreneurial and collaborative leadership. While entrepreneurial leadership promotes entrepreneurial agency and makes the university more entrepreneurial, collaborative leadership promotes collaborative agency and makes the university more engaged. This research unveils the ways to exercise these two types of leadership.